Leaf anatomy of Gaillardia cabrerae (Asteraceae): Basic plan and comparative study of two contrasting habitat populations - Beinticinco, Laura (2011)
This study evaluates the leaf anatomy pattern of Gaillardia cabrerae Covas, an exclusive endemic camephyte from the Lihué Calel National Park, province of La Pampa, Argentina. Leaf cross sections and peelings of plants growing in two different populations were used to determine the basic leaf anatomy patterns and to estimate the influence of growth conditions in the two microhabitats. The analysis showed differences in epidermal cells area, stomata density and main diameter, lacunar parenchyma cells and central vascular bundle diameter and palisade parenchyma cells dimensions. These aspects might be reflecting environmental conditions of the populations, especially sun exposure and soil moisture. The results provide information on the relationship of the species to its environment, which could be used in the establishment of conservation policies.